2016
DOI: 10.21767/2572-5459.100020
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Inclusion of Bio-Mos® in Milk or Milk Replacer Fed to Dairy Calves on Daily Weight Gain in the Pre-Weaning Period

Abstract: Objective: This meta-analysis determines the effect of BioMos ® , a mannan-oligosaccharide, supplementation to preweaned dairy source calves on average daily weight gain (ADG) pre-weaning. Methods:A literature search was performed and peerreviewed studies and abstract proceedings were included. Studies were included where Bio-Mos ® -supplemented calves were compared to control calves and weights were measured pre-weaning. A random effect meta-analysis was performed for overall effect and also comparing the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…The level of inclusion is one of the critical factors for measurable prebiotic effects in animals. Berge (2016) reported based on earlier experimental data, that MOS supplementation ranged from 2 to 10 g per day, with an average inclusion of 3.8 g per day. Heinrichs et al (2003) fed 77 mg MOS/kg initial body weight (BW) to their calves, while Hill et al (2008) used 137 mg MOS/kg BW.…”
Section: Introductionmentioning
confidence: 99%
“…The level of inclusion is one of the critical factors for measurable prebiotic effects in animals. Berge (2016) reported based on earlier experimental data, that MOS supplementation ranged from 2 to 10 g per day, with an average inclusion of 3.8 g per day. Heinrichs et al (2003) fed 77 mg MOS/kg initial body weight (BW) to their calves, while Hill et al (2008) used 137 mg MOS/kg BW.…”
Section: Introductionmentioning
confidence: 99%
“…As a typical kind of functional oligosaccharides derived from the cell wall of yeast, MOS is widely used in animal feed to promote nutrient digestibility and alleviate intestinal disease (Spring et al, 2015;Duan et al, 2016). This study was the first time to clarify the effects of Regarding the dose of MOS, there were significant variations in different studies, and it ranged from 1 to 10 g per day (Swanson et al, 2002;Berge, 2016). In the current study, the amount of MOS supplementation was 0.06% of BW in the colostrum or milk replacer (an average inclusion of 1.41 g per day, purity: 99%), which referenced from two previous studies of calves (Heinrichs et al, 2013;Tóth et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the dose of MOS, there were significant variations in different studies, and it ranged from 1 to 10 g per day ( Swanson et al, 2002 ; Berge, 2016 ). In the current study, the amount of MOS supplementation was 0.06% of BW in the colostrum or milk replacer (an average inclusion of 1.41 g per day, purity: 99%), which referenced from two previous studies of calves ( Heinrichs et al, 2013 ; Tóth et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that supplementing prebiotics (MOS and polysaccharides) to calves improves average daily gain and feed efficiency and decreases fecal shedding of pathogens [ 11 13 ]. Moreover, a meta-analysis indicated that MOS (commercial product Bio-Mos®) supplementation for dairy calves resulted in improved body weight gain [ 14 ]. However, recent evidence suggests that prebiotic supplementation (MOS and polysaccharides) has no effect on health or growth performance of calves [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%